Indikasi Perbuatan Melanggar Hukum Persaingan Usaha Pada Jasa Rapid Test Covid-19 Di Rumah Sakit - Fariz Seiff (Jurist-Diction, 2021)
AbstractRapid test is a means of conducting initial checks or examinations to find out whether a person is infected with the Covid-19 virus or not and there are many needs for transportation, agencies and exams that require rapid testing as their health protocol. The author, based on information from the business competition supervisory commission, found indications of violations of business competition law, namely the binding of a rapid test product with other laboratory tests. Here the author will discuss in terms of acts of breaking the law and violations of business competition law. With the formulation of the first problem is an act of violating the law on the covid-19 rapid test services in hospitals and the second is an indication of violations of business competition law in the covid-19 rapid test service in the hospital. The author uses a legal research method, uses a statutory approach and a conceptual approach. So that later it will be found whether there is a violation of the law if there is a binding of the rapid test. Keywords: Rapid Test; Tort Law; Competition Law.AbstrakRapid test sebagai sarana untuk melakukan pengecekan atau pemeriksaan awal untuk mengetahui apakah seseorang tertular virus covid-19 atau tidak dan banyak keperluan untuk transportasi, instansi hingga ujian yang mensyaratkan rapid test sebagai protocol kesehatannya. Penulis berdasarkan informasi dari komisi pengawas persaingan usaha menemukan adanya indikasi pelanggaran hukum persaingan usaha yakni pengikatan produk rapid test dengan tes laboratorium lain. Disini penulis akan membahas dari sisi perbuatan melanggar hukum dan pelanggaran hukum persaingan usahanya. Dengan rumusan masalah yang pertama adalah perbuatan melanggar hukum pada jasa rapid test covid-19 di rumah sakit dan yang kedua indikasi pelanggaran hukum persaingan usaha pada jasa rapid test covid-19 di rumah sakit. Penulis menggunakan metode penelitian hukum, menggunakan pendekatan perundang-undangan dan pendekatan konseptual.. Sehingga nantinya akan ditemukan apakah benar terdapat sebuah pelanggaran hukum jikalau benar terjadi adanya pengikatan dari rapid test tersebut.Kata Kunci: Rapid Test; Perbuatan Melanggar Hukum; Hukum Persaingan Usaha.